2012
DOI: 10.2139/ssrn.1996819
|View full text |Cite
|
Sign up to set email alerts
|

Value Added from Money Managers in Private Markets? An Examination of Pension Fund Investments in Real Estate

Abstract: Real estate is the most important alternative asset class for pension funds and represents on average more than five percent of their total holdings. We employ a previously unexplored international database to examine the investments of some 880 pension funds in direct real estate and REITs over the 1990-2009 period. We document that larger funds are more likely to invest in real estate internally, have lower costs, and higher returns. Smaller funds are more likely to invest in direct real estate, through exte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
11
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 52 publications
1
11
0
Order By: Relevance
“…Private pensions in our sample have a mean (median) size of $8.0 billion ($1.9 billion) and public pensions in our sample have a mean (median) size of $13.5 billion ($2.5 billion). The average size of pension funds in our sample is comparable to the $13.3 billion figure reported in Andonov, Eichholtz, and Kok (2013).…”
Section: Datasupporting
confidence: 75%
See 1 more Smart Citation
“…Private pensions in our sample have a mean (median) size of $8.0 billion ($1.9 billion) and public pensions in our sample have a mean (median) size of $13.5 billion ($2.5 billion). The average size of pension funds in our sample is comparable to the $13.3 billion figure reported in Andonov, Eichholtz, and Kok (2013).…”
Section: Datasupporting
confidence: 75%
“…However, despite focusing on the small sample of sophisticated (institutional) investors, we fail to find any evidence of FOFs outperforming hedge funds. 7 Our paper also contributes to the recent literature on the performance evaluation of institutional investors such as pension funds (Andonov, Bauer, and Cremers, 2012;and Andonov, Eichholtz, and Kok, 2013) and university endowment funds (Brown, Garlappi, and Tiu, 2010), and hiring and firing decisions of plan sponsors (Goyal and Wahal, 2008).…”
mentioning
confidence: 87%
“…In section 4, we explain the methodology employed. The empirical results are discussed in section 5 and section 6 concludes with a discussion of policy implications, including the recent 3 Other papers studying pension fund performance using the CEM database are Bauer, Cremers and Frehen (2010), Dyck and Pomorski (2011) and Andonov, Eichholtz and Kok (2012). Our findings are in line with the predictions of Brown and Wilcox (2009) and Lucas and Zeldes (2009) that accounting rules for U.S. public pension funds create a perverse incentive to invest more in riskier assets in order to discount liabilities at a higher rate.…”
mentioning
confidence: 99%
“…Finally, Andonov, Eichholtz and Kok (2012) analysed a database with pension fund allocations and costs. They showed that larger pension funds are more likely to invest in real estate internally, have lower costs and higher returns.…”
Section: The Inconvenient Truth About Feesmentioning
confidence: 99%